Application Of Distance Learning Through Learning Video Media To Increase Student Mathematics Learning Outcomes Class VI SD Negeri 022 Rambah Academic Year 2020/2021 - Hasrijal Hasrijal; Nur Arifin Adityo; Elyandri Prasiwiningrum (Indonesian Journal of Basic Education, 2021)
This study aims to determine the process of implementing distance learning with learning video media and improving mathematics learning outcomes for integer material. The research subjects were sixth grade students of SD Negeri 022 Rambah. The research subjects were 28 students consisting of 14 male students and 14 female students. The type of research used is Classroom Action Research (CAR) with Learning Video media. The data in this study are observations, documentation and tests. Research instrument in the form of observation sheets and test questions. Data analysis used qualitative description technique. Based on observations, it was found that in the process of learning mathematics, especially distance learning, students' learning motivation decreased. This resulted in student learning outcomes are not optimal, so teachers need to conduct Classroom Action Research. This Classroom Action Research is one of the efforts to improve mathematics learning outcomes. Based on the results of data analysis and discussion, it was concluded that the learning outcomes of mathematics in distance learning with learning video media increased. Based on the results of the study, it can be concluded that there is an increase in mathematics learning outcomes which is marked by an increase in the achievement of the KKM score, in the first cycle students who reach the KKM as much as 64.29% increase to 89.29% in the second cycle. Student activity and motivation also increased